2008
DOI: 10.2459/jcm.0b013e32830a6daf
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative angiotensin-converting enzyme inhibitors protect myocardium from ischemia during coronary artery bypass graft surgery

Abstract: ACE inhibitors prior to surgery confer added myocardial protection during surgical revascularization. Prospective, randomized clinical trials will be necessary to better define the role of ACE inhibitors in improving outcomes when they are prescribed prior to coronary artery bypass graft surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The authors concluded that off-pump could be a safe alternative to on-pump CABG without additionally increasing the risk of developing AKI in patients who would benefit from continued RAS inhibitor therapy. 4 This new evidence will encourage cardiac surgeons to use RAS inhibitors in OPCABG patients, but the other remarkable point is that mean arterial pressure was lower and the amount of norepinephrine infusion during operation was larger in patients who received RAS inhibitors than in those did not. Hypotension during positioning of the heart is a matter of concern during OPCABG.…”
Section: Article P 1852mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that off-pump could be a safe alternative to on-pump CABG without additionally increasing the risk of developing AKI in patients who would benefit from continued RAS inhibitor therapy. 4 This new evidence will encourage cardiac surgeons to use RAS inhibitors in OPCABG patients, but the other remarkable point is that mean arterial pressure was lower and the amount of norepinephrine infusion during operation was larger in patients who received RAS inhibitors than in those did not. Hypotension during positioning of the heart is a matter of concern during OPCABG.…”
Section: Article P 1852mentioning
confidence: 99%
“…1- 4 In the Effects of Quinapril on Vascular Angiotensin-Converting Enzyme and Determinants of Ischemia trial, patients were randomized 4 weeks before CABG to receive either quinapril (40 mg/day) or placebo for 1 year after surgery. 1 Patients treated with quinapril had a 77% reduction in ischemic events (death, revascularization, myocardial infarction, recurrence of angina pectoris, ischemic stroke, or transient ischemic attack stroke; 15% vs 4%; P=0.04).…”
mentioning
confidence: 99%
“…The pathophysiology of CSA-AKI is multifactorial and results from vascular and tubular injury, ischemia and reperfusion injury, neurohumoral activation, inflammation, (12)(13)(14). The patient was also on a statin before surgery.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…With regard to observational studies, Benedetto et al 50 found in a retrospective study (n¼481) that ACE inhibitors before surgery confer added myocardial protection (reducing cardiac troponin release) in patients undergoing CABG. Further evidence supporting the beneficial effects of the ACE inhibitor ramipril in reducing/preventing cardiovascular events comes from the landmark Heart Outcomes Prevention Evaluation trial, which included 9297 patients with high risk of CVD.…”
Section: )mentioning
confidence: 99%